ANALYSIS OF CONTROL SYSTEM OF INTERNAL REVENUE CASH Case study: CV. ARTHA TUNAS JAYA YOGYAKARTA - Ambrawati, Yuvita; Nursasmita, Akt., Drs. H. Irfan (Accounting, 2009)
To maintain the company´s business and its objectives to be achieved, every company requires the provision of adequate information. So to retain the viability of a company must create a good system as the information needed to deal with something that is repeatedly and routinely occur. A good system is a group that consists of the parts (functions, people, activities and so on) that form a network of procedure made under a unified pattern to perform basic activities of companies in which to perform its functions properly in accordance with its function which is closely related to each other between one another and cooperate with each other by a specific process to achieve a certain goal In the accounting system known as the control system inetern. Internal controls are not limited only to the plan of organization, but also the procedures and records relating to the decision process that leads to management authorization for the transaction. Authorization is a management function that is directly associated with the responsibility for achieving organizational goals and is a starting point to establish accounting control over the transaction. (Dr.Indra Bastian, 2001) A company´s profits through business process that is their revenue cycle. In a very simple form of the revenue cycle is a direct change of the final product and services into cash or cash. In addition to the company´s business goals is to obtain profit, because profit is the basic life of a business enterprise, but the success of a company is supported by a system that will form it, so that business can take place effectively and efficiently. With the system also can know the extent to which the human resources within a company´s performance membankun well, so that business continuity is maintained and has a bright prospect in the future. A system that will be formed is strongly influenced by the control environment that reflects the overall attitude, awareness, and actions of the board of commissioners, management, owners, and others about the importance of controls and its emphasis on the work unit concerned. The larger the scope and ukurann companies, resulting in many ways the management can not control directly or personally to the way the company´s operations, the companies need internal control systems as precise information which can be responsible for the reliability and accuracy. With a company´s internal control system will give at least on the organizational structure, task organization, and primary responsibility is to maintain the security of company property and to prevent errors that intentional or unintentional, fraud, and irregularities in the company of each organizational unit can be solved. In addition to maintaining the security of property companies´ internal control also aims to check the accuracy and reliability of accounting data, improve business efficiency to avoid unnecessary multiple jobs, and prevent the waste of all aspects of business including the prevention of the use of inefficient sources of funds. Internal Pengendaliaan also be used to encourage compliance with management policies that have been determined. Thus, the system of internal control provides assurance that the procedures and regulations can be implemented in accordance with a predetermined. Internal control system within an enterprise and terbankun not happen by chance but required a commitment of responsibility and awareness among top management as responsible for managing the funds entrusted by its owners, directors, and employees who are competent and honest as the perpetrator in carrying out operational activities of the company.